Parameter evaluation and fully-automated radiosynthesis of [(11)C]harmine for imaging of MAO-A for clinical trials - Philippe, C. (Appl Radiat Isot, 2015)
The aim of the present study was the evaluation and automation of the radiosynthesis of [(11)C]harmine for clinical trials. The following parameters have been investigated: amount of base, precursor concentration, solvent, reaction temperature and time. The optimum reaction conditions were determined to be 2–3 mg/mL precursor activated with 1 eq. 5 M NaOH in DMSO, 80 °C reaction temperature and 2 min reaction time. Under these conditions 6.1±1 GBq (51.0±11% based on [(11)C]CH(3)I, corrected for decay) of [(11)C]harmine (n=72) were obtained. The specific activity was 101.32±28.2 GBq/µmol (at EOS). All quality control parameters were in accordance with the standards for parenteral human application. Due to its reliability and high yields, this fully-automated synthesis method can be used as routine set-up.